2007
DOI: 10.1080/03640210701530748
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Linguistic Aspects of Visual Imagery in Sentence Comprehension

Abstract: There is mounting evidence that language comprehension involves the activation of mental imagery of the content of utterances (Barsalou, 1999;Bergen, Chang, & Narayan, 2004;Bergen, Narayan, & Feldman, 2003;Narayan, Bergen, & Weinberg, 2004;Richardson, Spivey, McRae, & Barsalou, 2003;Stanfield & Zwaan, 2001;Zwaan, Stanfield, & Yaxley, 2002). This imagery can have motor or perceptual content. Three main questions about the process remain under-explored, however. First, are lexical associations with perception or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
197
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(214 citation statements)
references
References 46 publications
(154 reference statements)
11
197
3
3
Order By: Relevance
“…A number of findings suggest that people do spontaneously engage in imagery during language comprehension, and that processing language affects performance in subsequent perceptual tasks (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…A number of findings suggest that people do spontaneously engage in imagery during language comprehension, and that processing language affects performance in subsequent perceptual tasks (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…These approaches are supported by strong experimental evidence, for instance, on the details of visual simulations (e.g., Stanfield/Zwaan 2001;Richardson et al 2003;Bergen et al 2007) and motor simulations (e.g., Glenberg/Kaschak 2002;Taylor/Zwaan 2001). One of these approaches, the Language and Situated Simulation (LASS) theory Simmons et al 2008), is particularly relevant to the purposes of the present study, since it assumes that knowledge is represented by multiple systems, which is coherent with the theoretical background of the OSIVQ.…”
Section: Mental Simulations and Language Comprehensionmentioning
confidence: 65%
“…In subsequent studies showed that positive words direct attention upwards and negative words direct attention downward (similar to related effects in concrete domains, e.g., Bergen et al, 2007;Estes et al, 2008;Richardson et al, 2003). People were faster to indicate whether a letter presented on the top of the screen was a p or a q after evaluating a positive word, than after evaluating a negative word.…”
Section: Valencementioning
confidence: 99%
“…The critical difference between interference and facilitation seems to be the length of time between the presentation of the linguistic stimulus and the perceptual stimulus. If the visual brain areas are still busy representing the linguistic stimulus (e.g., between 50 to 200 milliseconds) then interference is more likely, but after the visual brain areas are no longer active, the previous visual representation of vertical or horizontal locations might facilitate recognition (for a discussion, see Bergen et al, 2007).…”
Section: Grounding Concrete Conceptsmentioning
confidence: 99%